Influence of green tea powder on the performance, nutrient utilisation, caecal microbiota profile and meat quality of broiler chickens - D.V. Thomas; A.L. Molan; Y. Singh; V. Ravindran (Journal of Applied Animal Nutrition)
This study assessed the influence of green tea powder diet supplementation on performance, nutrient utilisation, caecal microbiota profile and meat quality in broiler chickens. A total of 144, one-day-old broiler (Ross 308) chicks were allocated to 18 cages (eight broilers/cage) which were randomly assigned to one of three dietary treatments: a wheat-based basal diet or supplemented with one of two types of green tea; normal (N-GT) or selenium-rich (Se-GT) tea, at an inclusion rate of 1%. Bird performance, nitrogen-corrected apparent metabolisable energy (AMEn), and total tract digestibility of fat and starch were measured on d 7, 21 and 35. Effects on microbiota profile on d 7, 21 and 35 were determined in a cohort study. Green tea supplementation reduced (P<0.05) the weight gain and feed intake but improved (P<0.05) feed efficiency. Supplementation with N-GT increased the AMEn on d 7 and 21, and with Se-GT on d 7 (P<0.05). AMEn increased with age for all treatments. Fat digestibility increased (P<0.05) in birds fed N-GT on d 21 and Se-GT on d 7 and 21. Starch digestibility increased (P<0.05) on d 21 with N-GT supplementation and on d 7 with Se-GT supplementation. Carcass and breast meat yields were unaffected (P<0.05) by the dietary treatments. The abdominal fat pad decreased (P<0.05) in the N-GT diet and numerically in the Se- GT diet. Drip loss was less in meat from birds (P<0.05) fed both green tea treatments. Cooking loss was reduced in the Se-GT treatment (P<0.05). Dietary inclusion of green tea powder positively influenced microbiota profile, with increased (P<0.05) numbers of beneficial bacteria (Lactobacillus spp. and Bifidobacterium spp.) and reduced (P<0.05) numbers of pathogenic bacteria (Clostridium spp. and Bacteroides spp.). Differences were observed between the two green tea types, with Se-GT being more beneficial than N-GT in the positive modulation of intestinal microbiota.